Simulation of reasonable shut-in time for shale oil after volume fracturing - LIAO Kai, ZHANG Shicheng, XIE Bobo (Youqicang pingjia yu kaifa)
To address issues such as the significant variance in shut-in effects between wells and the unclear effectiveness and timeliness of shut-ins during fracturing in shale formations, a numerical model integrating fracturing, shut-in, and production processes was developed. This model considers the synergistic effects of fracture closure, oil-water imbibition replacement, and fracturing fluid retention. The model's reliability was verified through simulations, exploring the oil-water migration law in the formation during the shut-in period of shale oil fractured wells and determining the optimal shut-in duration. Research indicates that: ① The oil-water migration characteristics during well shut-in undergo phased changes over time, which can be categorized into three main control stages: fracture closure, imbibition replacement, and energy balance. Additionally, these migration laws are closely related to the complexity of hydraulic fractures in space. ② Under the influence of capillary imbibition, extending the shut-in time appropriately benefits the initial production of fractured wells. However, an increase in fracturing fluid retention within the matrix can also exacerbate oil phase permeability damage. Based on the law of change in incremental oil volume, a reasonable shut-in time is identified to be between 30 to 45 days. ③ Considering real working conditions, “fracturing & well shut-in time” is proposed as an indicator for optimizing well shut-in, which aims to improve time efficiency and reduce differences between wells. This paper proposes an evaluation method and simulation workflow for assessing the well shut-in effects of volume fractured horizontal wells, offering valuable guidance in optimizing the reasonable shut-in time for shale oil fractured wells.